UI/UX Design of the Sigmawave Website Using the Design Thinking and Design Sprint Methods (Case Study of PT. Blue Silo Pte. Ltd) - Hardi, Andreas David DL; David, Felix (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Marketing is a crucial aspect of any business in the modern era that can make or break a company. Good User Interface (UI) design is essential to present information to users in an engaging yet meaningful manner. PT Blue Silo Pte. Tempo Communications Pte. A modern UI update was required for Sigmawave to support new features and enhance the experience. Designing the Sigmawave interface with Design Thinking and Design Sprint methodologies This study proposes. This process allows designs to emerge quickly that truly align with user requirements. Data was collected through open-ended interviews and surveys, where usability was assessed using the System Usability Scale. The research process consisted of user research, problem definition, ideation and prototyping, and solution validation. These designs have enhanced the user experience and also provided more assistance to the company’s marketing strategy with a simpler yet appealing front-end